Chapter La presenza della cultura italiana in riviste letterarie croate tra Ottocento e Novecento - Krpina, Zdravka (Biblioteca di Studi Slavistici, 2019)
This work explores the relationship between Croatia and Italy in a study of literary journals extending from the period of the Illyrian movement to Modernism (1835-1903). Moving away from a national and philological approach, we focus on interculturality and imagology. Our conclusions unfold at the intersection of these two fields, as well as "at the edge of literature and philosophy" (in Derrida's terms), where the relationship between Croatian and Italian cultural has been shaped according to various factors - literary, political, historical and also psychological.